(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
In recent years, the rising costs associated with in vitro fertilization (IVF) have become a significant concern, limiting access to assisted reproductive technologies for many aspiring parents. The rising financial burden on patients seeking assisted reproductive technologies necessitates a focused exploration of potential causes and strategic interventions to make IVF more economically accessible. The escalating cost of IVF poses a multifaceted challenge rooted in several contributing factors. Advances in reproductive technologies, the need for specialized medical expertise, and stringent regulatory requirements collectively drive up the overall expenses associated with IVF procedures. Increased demand for specialized personnel, sophisticated laboratory equipment, and adherence to stringent quality assurance measures. Moreover, the intricate nature of IVF procedures, coupled with the need for extensive hormonal stimulation and monitoring, adds to the economic burden on both healthcare providers and patients. There is a need to delve into pragmatic approaches to lower IVF costs, emphasizing collaboration and innovation. Optimization of laboratory processes, integration of artificial intelligence for predictive modeling, and standardization of protocols to streamline procedures without compromising success rates. Additionally, discussions encompass potential collaborations between the public and private sectors to foster shared responsibility and explore avenues for cost sharing. By fostering collaborative efforts and implementing innovative strategies, the aim is to make assisted reproductive technologies more financially feasible for a broader spectrum of individuals, ultimately advancing accessibility and affordability in reproductive medicine.